The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12893-021-01166-7
|View full text |Cite
|
Sign up to set email alerts
|

Permanent stoma: a quality outcome in treatment of rectal cancer and its impact on length of stay

Abstract: Background This study aimed to identify socioeconomic predictors of permanent stoma in rectal cancer treatment and examine its association with length of stay at the treatment facility. Methods Rectal cancer patients who underwent elective surgery between January 2015 and December 2018 were identified from the Agency for Health Care Administration Florida Hospital Inpatient Discharge Dataset. Multivariate regression models were utilized to identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Compared with the example of postoperative mortality, stoma-free survival is a complex endpoint affected by more factors than this study could capture. For example, defunctioning stomas will not be closed in patients with RC with progressive disease after surgery, 48,49 which could have modestly affected stoma-free survival in the current study. Moreover, socioeconomic status and cultural and geographical differences, such as acceptance of stomas and availability of stoma care, could have influenced decision-making.…”
Section: Discussionmentioning
confidence: 91%
“…Compared with the example of postoperative mortality, stoma-free survival is a complex endpoint affected by more factors than this study could capture. For example, defunctioning stomas will not be closed in patients with RC with progressive disease after surgery, 48,49 which could have modestly affected stoma-free survival in the current study. Moreover, socioeconomic status and cultural and geographical differences, such as acceptance of stomas and availability of stoma care, could have influenced decision-making.…”
Section: Discussionmentioning
confidence: 91%
“…This is important because the decision regarding which operation to perform considers several different factors including the location (height from anal verge) and staging of the tumor, comorbidities, likely functional outcome, response to neoadjuvant therapy, patient preference, and surgical experience/skill. The wider literature has demonstrated that disparities in stoma formation may also reflect socio‐demographic and geographic differences across populations 25 …”
Section: Methodsmentioning
confidence: 99%
“…The wider literature has demonstrated that disparities in stoma formation may also reflect socio-demographic and geographic differences across populations. 25 Persistent stoma at 18 months after anterior resection…”
Section: Circumferential Resection Margin Statusmentioning
confidence: 99%
“…Gastrointestinal diseases and their treatments commonly influence body image and self-esteem, which in turn can negatively affect sexual desire [160][161][162] . For example, patients with gastrointestinal diseases might have an ostomy or stoma as a result of disease and/or treatment [163][164][165][166] .…”
Section: Decreased Sexual Desirementioning
confidence: 99%
“…Approximately 80% of patients with colon cancer undergo surgery 283 and patients with rectal cancer are treated with multimodality therapy, including combinations of systemic therapy, radiotherapy and surgery, depending on disease extent and biomarkers 284 . The probability of a permanent ostomy for patients with CRC who undergo surgery ranges from 10% to 30% 164 , with up to 21% of patients with rectal cancer who undergo surgery requiring a permanent stoma 165 . In a survey study of 418 survivors of CRC of varied sexual orientations, 70% of patients reported issues with sexual desire 285 .…”
Section: Colorectal Cancermentioning
confidence: 99%